2019
DOI: 10.1097/bot.0000000000001493
|View full text |Cite
|
Sign up to set email alerts
|

Validation of PROMIS Physical Function Instruments in Patients With an Orthopaedic Trauma to a Lower Extremity

Abstract: Objectives: To evaluate the reliability, convergent validity, known-groups validity, and responsiveness of the Patient-Reported Outcomes Measurement Information System (PROMIS) Mobility Computer Adaptive Test (CAT) and PROMIS Physical Function 8a Short Form. Design: Prospective cohort study. Setting: Two Level-I trauma centers. Patients: Eligible adults with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…Finally, convergent validity between the UE v2.0 item bank was evaluated. Previous studies have found that PROMIS PF measures highly correlate with non-PROMIS measures (generally r > 0.80) [16, 18, 24, 25]. In the full bank dataset, the Flexilevel Scale of Shoulder Function Short Form (FLEX-SF) [34] and PROMIS PF v2.0 Short Form 8b (PFSF8b) were co-administered with the candidate UE item bank.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, convergent validity between the UE v2.0 item bank was evaluated. Previous studies have found that PROMIS PF measures highly correlate with non-PROMIS measures (generally r > 0.80) [16, 18, 24, 25]. In the full bank dataset, the Flexilevel Scale of Shoulder Function Short Form (FLEX-SF) [34] and PROMIS PF v2.0 Short Form 8b (PFSF8b) were co-administered with the candidate UE item bank.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have evaluated the comparability for Mobility items and UE items in relation to overall PROMIS-PF. Scores were exchangeable in a sample of lower extremity trauma patients (correlation between Mobility-CAT and the 8-item short form [PFSF8a v1.0] was 0.91; mean difference approximately 1 T-score [24]). Scores were not exchangeable for other populations, including upper extremity trauma patients (correlations have ranged from 0.64 to 0.87 between the UE v1.0–v1.2 and PF scores [18, 19, 25]; with a mean score difference of approximately 8 T-score points favoring better outcomes on the PFSF8a than the UE-CAT for trauma patients [25]).…”
Section: Introductionmentioning
confidence: 99%
“…19 This suggests convergent validity and is consistent with previously published studies of patients with lower extremity fractures and multiligamentous knee injuries. 16,17 PROMIS Mobility correlated to a lesser extent with SANE and PROMIS PI scores, an expected finding that suggests divergent validity. Additionally, the test burden of the PROMIS Mobility instrument was low, with patients answering a mean of 4.7 items, comparatively fewer than the 19 items (10 questions with 1 question having 9 and 1 having 2 subsections, respectively) required to complete the IKDC.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings also suggest that PROMIS Mobility is by traditional definitions inclusive in preoperative patients with ACL tears, because there were no floor or ceiling effects meeting the !15% conventional threshold of significance, consistent with other recently published studies. 16,17 In this study, we used an injured preoperative cohort of patients who are expected to return to a higher level of functioning after surgery. As such, the potential exists for ceiling effects at postoperative follow-up time points.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is not clear if these instruments evaluate all relevant concepts of interest (COI) to lower extremity trauma patients who undergo either reconstruction or amputation. 8,10,11 Therefore, while previous studies evaluating outcomes in this patient population have been rigorous and well designed, it is not clear if the outcomes measured reflect what is actually important to these patients.…”
mentioning
confidence: 99%